IN VITRO EVALUATION OF ANTI-OXIDANT PROPERTIES OF CUCUMIS MELO L. EXTRACTS OF LEAVES AND FRUIT - T. MURALI KRISHNA; SHIVA D.; KEERTHI D.; NANDINI A.; ASWAQ. AHMED; VIJAYA BHASKAR REDDY T.; KUMAR A. (International Journal of Pharma and Bio Sciences, 2013)
The main objective of this study is to evaluate the anti-oxidant properties in methanolic extract of Leaves and fruit of cucumies melo () The methanol leaf extract noticed significant scavenging activity on DPPH, superoxide, nitric oxide , hydrogen peroxide and hydroxyl radical. The total phenolic compounds were found to be high with leaves rather than the flesh of fruit.